Characteristics of invasive alien plants in different urban areas: the case of Kunshan City, Jiangsu Province, China - Liu, Yubing; Ren, Yueheng; Zhang, Hua; Qiu, Dongdong; Zhu, Yanpeng (Frontiers in Plant Science, 2025)
As globalization progresses, the threat of invasive alien plants to ecosystems is becoming increasingly prominent, and the negative effects of these plants on human health and socioeconomics are gradually increasing with the development of cities; thus, concern about the problem of invasive alien plants in cities is gradually increasing. In this context, we analyzed the differences in the distribution characteristics of invasive alien plants in urban green space, countryside and farmland in Kunshan city, which is located in the Yangtze River Delta region, an area characterized by rapid urbanization. Additionally, the relations between local plant diversity and the intensity of human activities on invasive alien plants were explored. The following results were obtained: (1) There are 38 species of invasive plants in Kunshan, among which 9 species, such as Alternanthera philoxeroides and Erigeron canadensis, are distributed in all kinds of urban areas. There are no endemic invasive plants in the urban green space; however, Amaranthus blitum and eight other species are distributed only in the countryside, and seven species, such as Bidens pilosa, are found only in farmland areas. (2) In different urban areas, native plant species and phylogenetic diversity vary in their resistance to invasive alien plants. Compared with those in other areas, the coverage and importance values of alien invasive plants in the urban countryside significantly decreased with increasing quantity of native plant species and phylogenetic diversity. (3) GDP per capita, the proportion of built-up land and road density were the main factors affecting the distribution of invasive alien plants, but there were differences in the influence of human activities in different urban areas. The importance values of invasive alien plants increased significantly with increasing population density and GDP per capita in the countryside, but there was no such trend in urban green space or farmland areas. Overall, these findings suggest that urban planning and landscape management strategies should target the management of invasive alien plants based on the characteristics in different urban areas to maintain the stability and sustainability of urban ecosystems.